THE CORRELATION OF OBTAINING GOOD ENGLISH GRADE WITH THE ACCURACY COMPLETION TIME FOR 2014 NURSES STUDENTS AT THE MOLUCCAS CHRISTIAN UNIVERSITY OF INDONESIA: Korelasi Pemerolehan Nilai Bahasa Inggris yang baik dengan Ketepatan Penyelesaian Masa Studi Mahasiswa Keperatawan Angkatan 2014 pada Universitas Kristen Indonesia Maluku - Harsono, Debora (Uniqbu Journal of Social Sciences, 2021)
This research aims to analyse about the Correlation of Obtaining Good English Grade with the Accuracy Completion Time for 2014 Nurses Students at Moluccas Christian University of Indonesia. To achieve the credibility of data for this research, a sequence of processes of data collection was conducted, namely : interview, transcript data students, fill in the questionnaire. The method that written uses is a descriptive study. The findings of this research consists of : the Correlation of Obtaining Good English Grade with the Accuracy Completion Time for 2014 Nurses Students at Moluccas Christian University of Indonesia. Besides, the nursing students affected by the external factors like, the students did not feel comfortable with the environment, especially with some lecturers and the method used by the lecturers were not interest, also the students were not supported by their parents, family, friends, to finish their study with the accuracy time. Shortly, the writer can conclude that there is the Correlation of Obtaining Good English Grade with the Accuracy Completion Time for 2014 Nurses Students at Moluccas Christian University of Indonesia.